Ativação alcalina de blocos de terra crua - Félix, Adriano Da Silva (2016)
Adobe is one of the first building materials used by man and returns to be sought today because its low environmental impacts. However, traditional adobe has as limitations its susceptibility to water action. Generally, to improve the mechanical and durability properties, chemical stabilizers as cement and lime are used, but as adobe are made of clays such products, to be effective, need to be employed in relatively large amounts (6%, 8%, 10% or more) which affect the sustainable character of the material. This work intends to use an innovative new chemical stabilization method that is known as alkaline activation. Binder percentages involved drop to 2% or 3%. In the process, silica and alumina from mineral sources react when exposed to a high alkalinity environment, forming an alternative binder having good mechanical properties. In this work, silica and aluminium sources were from Metakaulin and red ceramic waste. To provide necessary alkalinity sodium silicate is used. But it has high price. In this investigation different alkaline solutions were developed to replace the industrialized material. Adobes were produced and subjected to curing in electric oven and also in a solar greenhouse. Materials characterization tests as particle size, x-ray fluorescence (XRD), x-ray diffraction (DRX) and pH were performed. To see the viability of adobes as a component or masonry, compression strength test were performed. Also the, resistance to the action of water, weight loss, immersion absorption, weight loss by erosion were investigates. Chemical characterization (XRD and XRF) and electron microscopy (SEM) were made. The adobes stabilized with alkaline activation showed very good performance, and had compression strength ranging from 1.5 MPa to 6.1 MPa, depending on its composition. Regarding durability, alkali stabilized samples had better performance than reference and Portland cement stabilized samples. Thus, the alkaline stabilization represents a modern way to improve properties of the millenary adobe blocks.